Plasma assisted immobilization of TiO2 nanoparticles onto PLA surface to promote the antimicrobial activity - Chonlada Theerakarunwong (2018)
© 2014, Chiang Mai University. All rights reserved. Recently, there has been a trend for the application of antimicrobial and biodegradable materials for development of smart packaging products. Iron (III) ion (Fe3+) doped TiO2 nanoparticles were immobilized onto PLA film surface in order to enhance the antimicrobial efficiency. Fe3+ doped TiO2/PLA was prepared by a wet-impregnation method and characterized by XRD and SEM. High-resolution X-ray photoelectron spectroscopy for chemical analysis confirmed the higher presence of TiO2 nanoparticles deposited onto the SiOx plasma treated-PLA surface than the Ar plasma treated-PLA surface and untreated PLA surface, respectively. The plasma process generates active sites on PLA surface and renders strong interaction between NPs and surface, especially in SiOx plasma due to the reactive functional groups such as Si-O or silane groups. Both Ar/PLA/Fe/TiO2 and SiOx/PLA/Fe/ TiO2 showed the higher antibacterial efficiency of Fe3+ doped TiO2 than bared TiO2 owing to Fe ions might be reduced the width of the energy gap of TiO2.Fe3+ dopant created a stronger interaction between TiO2 and the PLA surface compared to bare TiO2 both on Ar and SiOx plasmas. Both Ar/PLA/Fe/TiO2 and SiOx/PLA/Fe/TiO2 showed the higher antibacterial efficiency of Fe3+ doped TiO2 than untreated PLA/Fe/TiO2 due to the higher concentration of nanoparticles attached on PLA surface, which could be influence the strong covalent interaction bonds between modified surface and particles.